2008
DOI: 10.1007/s00244-008-9149-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Effects of Buprofezin on Fecundity, Growth, Development, and Predation of the Wolf Spider Pirata piratoides (Schenkel)

Abstract: The toxicological effects of buprofezin, an insect growth regulator, on the fecundity, development, and pest control potential of the wolf spider Pirata piratoides (Schenkel) (Araneae: Lycosidae) were investigated in the laboratory. It was shown that buprofezin had low toxicity to P. piratoides and that the median lethal dosage (LD(50)) 48 h and 10% lethal dosage (LD(10)) after topical application for female spiders were 653 and 316 mg buprofezin/mg fresh weight of spider, respectively. Buprofezin significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Development should be affected more by insect growth regulators than by neurotoxic pesticides. However, application of buprofezin did not cause ontogenetic disruption in the two lycosids P. piratoides 90 and P. pseudoannulata 37. But the application of azadirachtin had similar effects to those reported for pesticides:97, 98 reduced growth and the occurrence of deformations in the ontogenetic development of the lycosid Schizocosa humilis (Banks, 1892) 61.…”
Section: Direct Effectsmentioning
confidence: 82%
See 1 more Smart Citation
“…Development should be affected more by insect growth regulators than by neurotoxic pesticides. However, application of buprofezin did not cause ontogenetic disruption in the two lycosids P. piratoides 90 and P. pseudoannulata 37. But the application of azadirachtin had similar effects to those reported for pesticides:97, 98 reduced growth and the occurrence of deformations in the ontogenetic development of the lycosid Schizocosa humilis (Banks, 1892) 61.…”
Section: Direct Effectsmentioning
confidence: 82%
“…Pesticides were found to decrease prey capture efficiency in a number of different species: in the linyphiid Hylyphantes graminicola (Sundevall, 1830) after application of methamidophis;59 in the lycosid Pirata piratoides (Bösenberg & Strand, 1906) and the linyphiid U. insecticeps after buprofezin application;89, 90 in the araneid Alpaida veniliae (Keyserling, 1865) after glyphosate application;91 in the lycosid P. pseudoannulata after imidacloprid application;68 in another lycosid P. amentata following application of cypermethrin;82 in the philodromid P. cespitum after exposure to diflubenzuron, neem, spinosad and acetamiprid;92 in the two linyphiids Erigone atra Blackwall, 1833 and O. apicatus after fenvalerate spray;80 in the araneid Neoscona pratensis (Hentz, 1847) after spinosad application;93 and in the lycosid Pardosa sp. after λ‐cyhalothrin spray 56.…”
Section: Direct Effectsmentioning
confidence: 99%
“…Valle et al (2002) recorded that buprofezin prevents the adult emergence from the pseudopupa of B. tabaci. Deng et al (2008) found that buprofezin significantly reduced the percentage hatching of spiders' eggs but had only a slight effect on the egg production. Hoffmann et al (2009) found that thiamethoxam reduced larval emergence rates by > 90% for all life stage targets in Plum curculio.…”
Section: Pesticides It Is Logical That Pbo Increases the Toxicity Ofmentioning
confidence: 94%
“…The authors found that lambda-cyhalothrin was highly effective in dryland Bacillus thuringiensis cotton compared with spinosad and thiodicarb. Deng et al (2008) stated that buprofezin had low toxicity to the wolf spider, Pirata piratoides. Gough and Wilkinson (1984) found that buprofezin was not effective against the cotton bollworm, Helicoverpa armigera, at any tested dose for any time of treatment in any spray.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Due to its widespread use, buprofezin residue has been frequently detected in food, soil, and drinking water (7)(8)(9)(10). Toxicity studies have shown that buprofezin is toxic to some aquatic organisms and nontarget insects (11)(12)(13)(14)(15). Buprofezin is considered to have low acute toxicity to humans and other mammals (acute rat oral 50% lethal dose [LD 50 ] is 1,635 mg · kg Ϫ1 in males).…”
mentioning
confidence: 99%